The enabling role of Configuration Management for the Systems Engineering of tomorrow's complex Systems and Systems of Systems. Issue 1 (13th September 2016) - D'Souza, Adriana; Kossmann, Mario; Watts, Stephen
Abstract: Times to market for complex Systems and Systems of Systems(SoS) in the aerospace and defence industries shall be reduced, whereas both customer expectations and technology evolutions are increasing at an exponential rate. As the total life cycle of complex Systems and SoS frequently spans across several decades, the customer expectations and market conditions are highly likely to evolve, thus their development needs to be kept in line with evolving business cases. Systems Engineering(SE) and Configuration Management(CM) need to work even more closely together in order to address this. CM as a discipline is essential for this as the key discipline for establishing traceability and controlling baseline evolutions and iterations between all the relevant pieces of information resulting from the related system lifecycle processes. This paper provides an outlook on how CM may enable SE of tomorrow's complex Systems and SoS, including some key recommendations and related challenges.